2018
DOI: 10.3168/jds.2017-14372
|View full text |Cite
|
Sign up to set email alerts
|

Variation in fibroblast expression of toll-like receptor 4 and lipopolysaccharide-induced cytokine production between animals predicts control of bacterial growth but not severity of Escherichia coli mastitis

Abstract: Mastitis caused by environmental pathogens such as Escherichia coli is highly problematic to the dairy industry because it incurs substantial cost and tends to be difficult to manage. An effective innate immune response by the host is key to controlling infection, but it should also limit collateral damage to the mammary gland. Between-animal differences in mastitis severity have been attributed to variability in the innate response. In the current study, we used primary dermal fibroblast as a model to rank an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…On the other hand, the role of leukocytes as first line responders is important, and maintenance of a certain level of neutrophil infiltration is essential for the phagocytosis and elimination of bacteria from the mammary gland to cure mastitis (Aitken et al, 2011). Therefore, chemoattractants are of importance for the mammary immune response, and Korkmaz et al (2018) found that cows with greater production of milk IL-8 were more capable of limiting bacterial growth during mastitis than cows with lower milk IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the role of leukocytes as first line responders is important, and maintenance of a certain level of neutrophil infiltration is essential for the phagocytosis and elimination of bacteria from the mammary gland to cure mastitis (Aitken et al, 2011). Therefore, chemoattractants are of importance for the mammary immune response, and Korkmaz et al (2018) found that cows with greater production of milk IL-8 were more capable of limiting bacterial growth during mastitis than cows with lower milk IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, TLR2 identifies cell wall components of gram-positive bacteria [ 40 , 41 ], whereas TLR4 identifies LPS from gram-negative bacteria [ 16 , 42 ]. Studies show that TLR4 is the main pattern recognition receptor in response to E. coli -induced mastitis in mice, goats and dairy cows [ 43 , 44 , 45 ]. We found that E. coli –induced an up-regulation of Tlr4 in PMECs at 6 h after E. coli infection.…”
Section: Discussionmentioning
confidence: 99%
“…In the production process, mastitis is still not fully controlled despite thorough hygiene, antibiotic treatment, vaccination, and other measures (52). Therefore, the association between dairy cows' genetic variation and mastitis is receiving more and more attention (18, 35, 53, 54). This study sought to screen for significant differential SNPs associated with clinical mastitis via GWAS-2bRADseq, to identify potential clinical mastitis susceptibility or resistance genes and to verify for their authenticity and role in mastitis resistance/tolerance in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%